Adaptive Management in the Implementation of Full-Day School - Moch. Zakki Mubarok; Muhammad Lukman Khakim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2025)
Full-Day School (FDS) in Islamic elementary education requires adaptive management grounded in instructional leadership theory to integrate academic and religious learning within extended daily schedules. This study analyzed the planning, implementation, and evaluation of the FDS program at SD Islam Plus Al-Haqiqi, Sidoarjo, as well as the supporting and inhibiting factors influencing its sustainability. Using a descriptive-qualitative approach with 32 purposively selected participants, data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using the Miles Huberman Saldaña interactive model. The findings reveal that participatory adaptive planning aligned the national curriculum with Islamic character education goals; teachers enacted dual roles as instructional leaders through flexible pedagogy and structured active breaks; and continuous adaptive evaluation enabled rapid instructional adjustments. Institutional commitment, teacher efficacy, and parental involvement supported the program, while limited infrastructure and student fatigue posed challenges. The study proposes an adaptive-leadership model for Islamic schools with limited resources and recommends the use of well-being-oriented evaluation instruments, targeted professional development in adaptive leadership, and appropriate educational technologies to strengthen the program’s long-term sustainability.